Statistics for business and economics - Sweeney, Dennis J.; Williams, Thomas A.; Anderson, David R. (Cincinnati : South-Western College, 1999)
Data and statistics. Descriptive statistics. Introduction to probability distributions. Sampling and sampling distributions. Interval estimation. Hypothesis testing.
Keywords: Methodology; Commercial statistics; Mathemetics; Statistical methods; Statistics; Economics -- Statistical methods; Commercial statistics -- Methodology